THE EFFECT OF ONLINE NEWSPAPER ON STUDENTS' READING COMPREHENSION AT ONE SENIOR HIGH SCHOOL IN PADANG - Gatot Hadi Waluyo (Langue (Journal of Language and Education), 2023)
One of the challenges to improving education quality is promoting reading and understanding of what is being read. Understanding reading skills is still a problem that is still crucial for language learners, especially in senior high school. Therefore, it is necessary to use interesting learning methods to help students improve their reading skills. In this regard, this study aims to know the effect of online newspapers to enhance students' reading skills. This study used experimental design. The researchers conducted this research at one of the senior high schools in Padang. A control class (n: 35) and an experimental class (36) were included in this study. then researchers use online newspapers originating from "TheJakartaPost" to teach experimental classes. At the same time, the chart is used as a teaching medium in the control class. Based on the findings. The researcher found a significant difference in the experimental class's pretest (76.10) and post-test (85.14) results. These results indicated a positive effect of online newspapers as media in reading achievement. Several recommendations and suggestions have been proposed for further studies to get more improvement.